(untitled) (Plant Tissue Culture and Biotechnology, 2008)
An efficient protocol was developed for in vitro propagation of Abrus precatorius L. through induction of indirect organogenesis in nodal segment derived callus tissue. Yellowish-green nodular callus was induced at the cut surface of the nodal segments cultured on MS fortified with 5.0 mg/l BAP and 0.5 mg/l NAA. The callus differentiated into adventitious shoots when it was subcultured on to MS supplemented with 3.0 mg/l BAP + 0.5 mg/l Kn + 0.5 mg/l NAA. On an average 6.87 Â± 0.26 shoots/culture developed. These microshoots were rooted in half-strength MS containing 1.0 mg/l IBA and the rooted plantlets were transferred to soil after proper acclimatization. Key words: Abrus precatorius, Medicinal plant, Callus culture, Propagation DOI = 10.3329/ptcb.v17i1.1121 Plant Tissue Cult. & Biotech. 17(1): 59-64, 2007 (June)